A pilot study of clinical results of Odyliresin (Iresine celosia) in symptomatic benign prostatic hyperplasia. (September 2017) - Porru, D; Franco, C Di; Bobbi, V; Tinelli, C; Rovereto, B
Aim: The aim of this pilot clinical trial was to determine if Odyliresin ( Iresine celosia ), a cytochrome-flavoprotein with a powerful anti-oxidant action on cells, has a therapeutic effect on benign prostatic hyperplasia-related lower urinary tract symptoms, reducing symptoms and prostate volume, improving the patient's quality of life and eventually limiting the number of patients who require surgery or endoscopy after medical treatment. Methods: Thirty patients with benign prostatic hyperplasia-related lower urinary tract symptoms were recruited and followed up. Primary outcomes were assessed using International Prostate Symptom Score symptom questionnaires, quality of life score, examination, prostate-specific antigen, transrectal ultrasound, uroflowmetry with post-void residual volume. Once recruited, patients were assigned for treatment: alpha-antagonist (alfuzosin 10 mg)+Odyliresin ( Iresine celosia ) 2 ml, 20 drops once daily. Results: The results for quantitative variables were expressed as mean values and standard deviation as they were all normally distributed (Shapiro–Wilk test). The study included 30 patients with an average age of 68 years (range 56–80 years). The statistical analysis of data reports significant improvement of mean values of maximum urinary flow rate (+1.2, p =0.050), average flow rate (+0.47, p >0.002), International Prostate Symptom Score (–4.8, p =0.000), quality of life (–1.4, p =0.000), total prostatic volume (–1.7, p =0.000), prostatic adenoma (–6.9, p =0.000) and post-void residual volume (–17.8, p >0.004) between baseline and 12 months after treatment. No patient had acute urinary retention during treatment or need for benign prostatic hyperplasia-related surgery at the end of the 12-month treatment. Conclusions: All patients with benign prostatic hyperplasia-related lower urinary tract symptoms received both alphalitic and Odyliresin treatment. Clinical parameters and uroflowmetry parameters significantly improved, adenoma volume and post-void residual volume were significantly reduced at 12 months. This is the first clinical experience with Iresine celosia, a phytotherapeutic agent with no scientifically proven clinical efficacy so far in benign prostatic hyperplasia.